GAMIFIKASI PEMBELAJARAN DI DUNIA VIRTUAL: STUDI KOMPARATIF PLATFORM METAVERSE TERHADAP E-LEARNING KONVENSIONAL - Dziqra Ananda Hersya; Tata Sutabri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Advances in information technology have had a significant impact on the transformation of the education system, including in terms of learning methods and media. One of the innovations that is currently developing rapidly is the application of gamification in metaverse-based learning. This study aims to compare the effectiveness of learning through gamification on the metaverse platform with conventional e-learning methods. Using a qualitative approach with a comparative study method, data were collected through classroom observations, interviews with students and teachers, and literature reviews. The results of the study indicate that gamification in the metaverse can increase learning engagement, motivation, and learning outcomes in a more significant way compared to traditional e-learning. These findings indicate the need for a new approach in designing a more interactive and immersive digital learning system.